Performance Of Islamic Mutual Funds In The Indonesian Capital Market - Yeni, Sela Rahma (Journal of Accounting and Management, 2024)
The purpose of this study is to analyze the performance of syariah mutual funds which include shares, fixed income, mixed and money markets. Type The research carried out was quantitative descriptive research. Method Data collection in this research is a documentation technique with data secondary, namely through the official site bareksa.com. Mutual fund performance measurement Syariah in this research uses only one method, namely the Sharpe method.Based on Sharpe's calculations it can be concluded that the highest performance in between sharia mutual funds which include shares, fixed income, mixed and the money market in 2015, 2016 and 2017 is syariah stock mutual funds.